Genome-Wide Identification and Expression Divergence of CBF Family in Actinidia arguta and Functional Analysis of AaCBF4 Under Cold Stress - Sumei Li; Qina Zhang; Zhenzhen Zhang; Peng Zhang; Congcong Li; Leiming Sun; Jinbao Fang; Ran Wang; Feng Wei; Yukuo Li; Miaomiao Lin; Xiujuan Qi (Life, 2025)
The C-repeat binding factors (CBFs) gene is essential for plants’ cold response, which could not only be induced by the inducer of CBF expression (ICE) genes but also activated the expression of the cold-regulated (COR) gene, thereby participating in the ICE-CBF-COR cold response pathway. However, this gene family and its functions in Actinidia arguta remain unclear. In this study, whole-genome identification and functional analysis of CBF family members in A. arguta were performed. Eighteen CBF genes, which were located on four chromosomes and had five tandem repeats, were identified. The proteins encoded by the genes were predicted to be located in the nucleus and cytoplasm. The results of the promoter cis-acting element analysis revealed light response elements, low-temperature response elements, and hormone (methyl jasmonate, gibberellin, salicylic acid, etc.) response elements. We analyzed collinearity with other kiwifruit genomes, and, interestingly, the number of CBF family members differed across geographic locations of A. arguta. RT-qPCR revealed that the expression of the CBF gene family differed under low-temperature treatment; specifically, we observed differences in the expression of all the genes. Based on phylogenetic relationships and RT-qPCR analysis, the expression of AaCBF4.1 (AaCBF4) was found to be highly upregulated, and the function of this gene in cold resistance was further verified via overexpression in transgenic Arabidopsis. AaCBF4-overexpressing plants showed higher tolerance to cold stress, showing a higher germination rate, higher chlorophyll content and lower relative electrolyte leakage. In addition, compared with the wild-type Arabidopsis, the overexpressing plants exhibited significantly reduced oxidative damage due to the reduction in reactive oxygen species production under cold stress. Therefore, AaCBF4 plays an important role in improving the cold resistance of Actinidia arguta and can be further used to develop kiwifruit germplasm resources with strong cold resistance.